Selective Hydrogenation of CO2 Using Ruthenium Nanoparticles Intercalated Montmorillonite Clay - Upadhyay, Praveenkumar R.; Srivastava, Vivek (Letters in Organic Chemistry, 2016)
We easily prepared the well characterized ruthenium nanoparticles intercalated montmorillonite clay catalyst to catalyze amine mediated CO2 hydrogenation to formic acid. Ru exchanged MMT clay was reduced under hydrogen atmosphere in PEG (400) solvent system to achieve the Ru metal nanoparticles with average 25.5±2 nm size within the interlayer spacing of MMT clay. 17 different cyclic and acyclic amines were studied for CO2 loading and further tested as the solvent system with ethanol for CO2 hydrogenation reaction. The corresponding hydrogenated product (formic acid) was obtained in high TON /TOF value with 40% ethanolic solution of tetraethylenepentamine. Six times catalyst recycling is the added advantage of this proposed reaction protocol.
Keywords: Carbon sequestration